IMPACT OF HUMAN INTERFERENCE ON FISH DIVERSITY IN FIVE WETLANDS OF NORTH BENGAL, INDIA - DATTA, TANMAY; DAS, DEBASHIS (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
This study was conducted in five wetlands of North Bengal to find out impact of anthropogenic activities in diversity of fish species. Total 101 fish species were documented in those wetlands. Maximum species (93) were recorded from Gajoldoba wetland, whereas Nimai beel recorded only 33 species. Results indicate that anthropogenic activities (other than fishing) affected ichthyofauna diversity adversely. Human interferences altered electrical conductivity, dissolved oxygen, BOD, free carbon dioxide, phosphate and nitrate level significantly. Also, human interferences significantly affected emergent vegetation covered shore area and percentage of floating vegetation. All those physio-chemical and vegetative changes possibly affected the zooplankton diversity negatively dwindling the base of the food chain and in turn, affected fish diversity. Immediate and proper action should be taken to save this biodiversity and the wetland of this region as a whole.